Sistem Penulangan pada Karakter 3D dalam Film Animasi The Relativity Of Reality - Abdulah Rosyidouddin El Islami; Charles De Haan (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Digital animation technology is increasingly advancing, as evidenced by the proliferation of animated films worldwide. This is also true in Indonesia, where the production of animated films has increased significantly due to the improvement and ease of digital animation technology. One of the most important parts of the animation process is the rigging process, which involves creating a skeleton for the character or object so that it can move and appear lifelike. The rigging process in the short animated film "The Relativity Of Reality" tells the story of Rei, a young boy who discovers advanced technology from a secret organization. However, the owner of the technology comes to take it back, leading to a struggle and chase. Rei decides to escape but is cornered and a battle ensues. The characters in the film are animated using rigging techniques, utilizing the Bendy Bone feature in the Blender application. This feature is useful in creating a rigged system for characters and objects. The result of applying rigging with the Bendy Bone feature is that characters move more fluidly, not only in the legs, body, and arms but also in the face. Therefore, the use of bendy bone and facial rigging in characters will make it easier to produce animations. In addition, rigging can also be applied to other moving objects such as cars, skateboards, doors, and cabinets.